2012
DOI: 10.3346/jkms.2012.27.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Morphine and Selective Serotonin Receptor Inhibitors in Rats Experiencing Inflammatory Pain

Abstract: Citalopram and paroxetine are selective serotonin reuptake inhibitors and also have antinociceptive effects. We investigated the antiallodynic and antihyperalgesic effects of intrathecally administered morphine, citalopram, paroxetine, and combinations thereof, in a rat model in which peripheral inflammation was induced by complete Freund's adjuvant (CFA). Drugs were intrathecally administered via direct lumbar puncture. Mechanical allodynia was measured using a Dynamic Plantar Aesthesiometer. Thermal hyperalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
4
12
0
Order By: Relevance
“…Furthermore, other adaptive changes within the CNS resulting from the continued receptor stimulation by morphine concern alterations in the expression of different proteins at the cellular level or modifications in the connectivity of neurons involved in the nociception transmission and/or supraespinal integration (Christie, 2008). The antinociceptive-like effect detected after the acute administration of citalopram observed in development of tolerance experiments (Figure 3) has not been consistently described in previous investigations regardless its possible participation as potentiator of morphine analgesia (Fasmer et al, 1989, Larsen and Christensen, 1982, Larsen and Hyttel, 1985, Lee et al , 2012, Sugrue, 1979. The reason for this discrepancy probably resides in the nature of the hot-plate nociception assay where…”
Section: Accepted Manuscriptmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, other adaptive changes within the CNS resulting from the continued receptor stimulation by morphine concern alterations in the expression of different proteins at the cellular level or modifications in the connectivity of neurons involved in the nociception transmission and/or supraespinal integration (Christie, 2008). The antinociceptive-like effect detected after the acute administration of citalopram observed in development of tolerance experiments (Figure 3) has not been consistently described in previous investigations regardless its possible participation as potentiator of morphine analgesia (Fasmer et al, 1989, Larsen and Christensen, 1982, Larsen and Hyttel, 1985, Lee et al , 2012, Sugrue, 1979. The reason for this discrepancy probably resides in the nature of the hot-plate nociception assay where…”
Section: Accepted Manuscriptmentioning
confidence: 71%
“…i.e. mianserin and methysergide, suggested the participation of 5-HT 2 receptor subtypes in these processes (Gatch et al, 1998, Lee et al, 2012. At this respect, we after sustained treatments (Berger andWhistler, 2010, Whistler, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…For example, administration of the 5-HT precursor 5-hydroxytryptophan (5-HTP) or an SSRI (fluoxetine, citalopram, or paroxetine) increases morphine antinociception in mice and rats, respectively (Dewey et al, 1970, Larson and Takemori, 1977, Hynes et al, 1985; Lee et al, 2012). Moreover, fluoxetine and the 5-HT releaser fenfluramine enhance the antinociceptive effects morphine in nonhuman primates (Gatch et al, 1998; Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental and clinical studies it has been found that antidepressants possess antinociceptive and analgesic properties and are therefore used in the combined therapy of chronic pain. 1 The serotoninselective reuptake inhibitors (SSRIs) were fi rst introduced as a new class of antidepressants at the end of 1980s and due to their favorable side-effect profi le have since become fi rst-line therapy of depressive disorders. 2 Most SSRIs have been found to also possess secondary binding properties -dopamine reuptake inhibition, noradrenaline reuptake inhibition, muscarinic cholinergic antagonism, etc.…”
mentioning
confidence: 99%